The Conners Continuous Performance Test CPT3™: Is it a reliable marker to predict neurocognitive dysfunction in Myalgic encephalomyelitis/chronic fatigue syndrome? - Fernández-Quirós, Judith; Lacasa-Cazcarra, Marcos; Alegre-Martín, Jose; Sanmartín-Sentañes, Ramón; Almirall, Miriam; Launois-Obregón, Patricia; Castro-Marrero, Jesús; Rodríguez-Urrutia, Amanda; Navarro-Sanchis, Jose A.; Ramos-Quiroga, J. Antoni (Frontiers in Psychology, 2023)
Introduction: The main objective is to delimit the cognitive dysfunction associated with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) in adult patients by applying the Continuous Performance Test (CPT3™). Additionally, provide empirical evidence on the usefulness of this computerized neuropsychological test to assess ME/CFS. Method: The final sample (n=225; 158 Patients/ 67 Healthy controls) were recruited in a Central Sensitization Syndromes (CSS) specialized unit in a tertiary hospital. All participants were administered this neuropsychological test. Results: There were significant differences between ME/CFS and healthy controls in all the main measures of CPT3™. Mainly, patients had a worse indicator of inattentiveness, sustained attention, vigilance, impulsivity, slow reaction time, and more atypical T-scores, which is associated with a very high likelihood of having a disorder characterized by attention deficits, such as Attention Deficit Hyperactivity Disorder (ADHD). In addition, relevant correlations were obtained between the CPT3™ variables in the patient's group. The most discriminative indicators of ME/CFS patients were Variability and Hit Reaction Time, both measures of response speed. Conclusions: The CPT3™ is a helpful tool to discriminate neurocognitive impairments from attention and response speed in ME/CFS patients, and it could be used as a marker of ME/CFS severity for diagnosing or monitoring this disease.